A criterion for Banach manifolds to be finite-dimensional - Savkin, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We extend the results obtained in [1] to the case of arbitrary Banach spaces and manifolds. We give an example of a continuous bijective mapping with discontinuous inverse which acts in a Banach space and differs from the identical mapping only in an open unit ball. A criterion for a Banach manifold to be finite-dimensional is established in terms of the continuity of inverse operators.